2022
DOI: 10.54648/trad2022003
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Australia-China Trade Tensions

Abstract: In 2020 Australia’s political relations with China plumbed new depths. Trade and other economic ties were also hit with disruption. Contributing to this deterioration, and complicating an accurate assessment of the consequences, has been a raft of misunderstandings. This article demystifies the bilateral trade tensions by exposing the deeper drivers of political friction, providing a critical assessment of the vulnerability of the Australian economy, and placing the current state of Australia’s relations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In terms of the changing trade patterns between China and Australia, compared to the outlook on the bright future of trade relations between the two countries at the beginning of this century, many scholars have pointed out the tension and degradation of bilateral trade between China and Australia in recent years, with the Sino-US trade war and the tension between China and Australia. Zhou [39] concluded that the China-Australia trade is tense by revealing the underlying factors. After peaking between 2013 and 2015, Australia-China relations declined sharply in 2017 [68].…”
Section: Comparison and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the changing trade patterns between China and Australia, compared to the outlook on the bright future of trade relations between the two countries at the beginning of this century, many scholars have pointed out the tension and degradation of bilateral trade between China and Australia in recent years, with the Sino-US trade war and the tension between China and Australia. Zhou [39] concluded that the China-Australia trade is tense by revealing the underlying factors. After peaking between 2013 and 2015, Australia-China relations declined sharply in 2017 [68].…”
Section: Comparison and Outlookmentioning
confidence: 99%
“…Nevertheless, Australia is too dependent on Chinese manufacturing goods. In the prospective analysis, researchers focus on the establishment of a China-Australia free trade area [37,38] and the deepening of the trade war [39] to explore where China and Australia will go on the trade road. In the product-specific analysis of China-Australia trade, researchers focus on essential commodities in China-Australia trade-such as agricultural products [30,40], livestock products [41,42], and iron ore [43]-and evaluate the fluctuation of trade intensity of these crucial commodities over time, along with the domi-nance overdependence in bilateral trade.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Australia's exports to China totalled US $102 billion, accounting for one‐third of Australia's total goods and services exports (The World Bank, 2020). However, China and Australia's political relationship has deteriorated since 2016, escalated by Australia's ban on Huawei's 5G network and China's antidumping investigation against Australian barley (BBC, 2018; Zhou & Laurenceson, 2022). The relationship further worsened in April 2020 after Australia proposed independent international investigations into COVID‐19's origins (ABC, 2020; Zhou & Laurenceson, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, China and Australia's political relationship has deteriorated since 2016, escalated by Australia's ban on Huawei's 5G network and China's antidumping investigation against Australian barley (BBC, 2018; Zhou & Laurenceson, 2022). The relationship further worsened in April 2020 after Australia proposed independent international investigations into COVID‐19's origins (ABC, 2020; Zhou & Laurenceson, 2022). In May 2020, China began imposing trade restrictions on Australian imports of barley, beef, coal, cotton, timber, copper and wine, significantly impacting both Australian and Chinese firms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation